Evolution of the health system of Equator, good practices and challenges in its construction in the last decade 2005-2014 - Chang Campos, Caroline J. (2018)
Introduction. Ecuador has undertaken important reforms in search of universality and equity however; the system continues fragmented and does not guarantee universal access. This study aims to address the evolution of the health system of the Ecuador in order to contribute with the process the country and the Region reform from the perspective of social representations Objective. Describe the governance, financing and provision of services related to political, social and economic factors, identify good practices, lessons learned and challenges in construction of the system. Methodology. Qualitative descriptive-interpretative study based on the Theory of Social Representations, through systematic review of documents and in-depth interviews with 14 actors involved in the reform process, which were codified, analyzed and interpreted, highlighting the majority perceptions, convergences and divergences. Results and Conclusions. The health system is universal and of free access by constitutional mandate. The social representations recognize the governance of the health authority that requires strengthening the leadership and legitimization on the part of the sector and of the civil society. Positioning Health as "right" and priority of the State, it has been one of the best "good practices", while the lack of social participation for the legitimization and validation of change processes is considered a lesson learned, since it is true the political, social and economic factors have been favorable for the transformation of the health sector since 2007. The alteration or setback of these factors would jeopardize the progress and consolidation of the Health System. The main challenge is the financial sustainability of universality and free of charge in line with quality, being necessary the rationalization of expenditure and the guided services to the care model based on primary health care.